Black towns, black futures : the enduring allure of a black place in the American West - Slocum, Karla, 1963- (The University of North Carolina Press, 2019)
"Beginning at the end of the Civil War and continuing for nearly fifty years, Oklahoma saw the settlement of over fifty unique towns with a common thread; in each of these towns, nearly every citizen was African American. Black town founders and residents, who were anxious to escape the racially hostile Deep South, built schools, banks, and churches, creating their own places of success and security. In this ethnographic study, Karla Slocum reveals the lasting importance of these all-black towns to Black Americans. Once considered icons of Black American economic and social achievement, these towns have been studied by historians, but here Slocum examines the present-day fascination they produce. Many of these towns still exist, though their populations have dwindled, and continue to hold an appeal for Black Americans seeking a safe and affirming residential space"--